Auxin: a molecular trigger of seed development - Figueiredo, D. D.; Kohler, C.
The evolution of seeds defines a remarkable landmark in the history of land plants. A developing seed contains three genetically distinct structures: the embryo, the nourishing tissue, and the seed coat. While fertilization is necessary to initiate seed development in most plant species, apomicts have evolved mechanisms allowing seed formation independently of fertilization. Despite their socio-economical relevance, the molecular mechanisms driving seed development have only recently begun to be understood. Here we review the current knowledge on the role of the hormone auxin for the initial development of the three seed structures and as a trigger of fertilization-independent seed development.
Keywords: AUXIN; SEED; ENDOSPERM; SEED; COAT; APOMIXIS; POLYCOMB GROUP